TELAAH DAMPAK NILAI-NILAI SUFISME DAN SOSIOLOGIS DALAM TRADISI BEQEN SEBAGAI KONSTRUKSI SOSIAL MASYARAKAT DESA PENE KECAMATAN JEROWARU - HABLUN ILHAMI (TASÂMUH, 2021)
The entry of new values in all lines of people’s lives has an impact on changes in the values of people’s lives. The entry of new values caused by modernization and globalization not only has a positive impact on people’s lives but on the contrary. The existence of local traditions and culture of the community then becomes important in building the social construction of the social life of the community. In the context of the Pene village community, the existence of the “Beqen” tradition becomes an institution that indirectly contains values that are references in building the life pattern of the Pene village community. This research uses qualitative research with sociological and phenomenological approaches. In collecting data related to researches, researches used observation and interview methods